2020
DOI: 10.1112/tlm3.12022
|View full text |Cite
|
Sign up to set email alerts
|

Twisted Eisenstein series, cotangent‐zeta sums, and quantum modular forms

Abstract: We define twisted Eisenstein series E ± s (h, k; τ) for s ∈ C, and show how their associated period functions, initially defined on the upper half complex plane H, have analytic continuation to all of C := C \ R 0. We also use this result, as well as properties of various zeta functions, to show that certain cotangent-zeta sums behave like quantum modular forms of (complex) weight s.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Remark. This new kind of quantum modularity was also noted by Bettin and Conrey in [3] where they computed E k (z) − z −k E k (− 1 z ) for any k ∈ C. Folsom has recently extended their work in [7], where it was shown that a new family of "twisted Eisenstein series" are holomorphic quantum modular forms, which were then used to show that certain cotangentzeta sums are quantum modular forms in the original sense. Zagier's presentation in [19] shows that for any γ = ( a b c d ) ∈ SL 2 (Z) that h E k ,γ (z) extends to a holomorphic function on the cut plane…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 65%
“…Remark. This new kind of quantum modularity was also noted by Bettin and Conrey in [3] where they computed E k (z) − z −k E k (− 1 z ) for any k ∈ C. Folsom has recently extended their work in [7], where it was shown that a new family of "twisted Eisenstein series" are holomorphic quantum modular forms, which were then used to show that certain cotangentzeta sums are quantum modular forms in the original sense. Zagier's presentation in [19] shows that for any γ = ( a b c d ) ∈ SL 2 (Z) that h E k ,γ (z) extends to a holomorphic function on the cut plane…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 65%